2017
DOI: 10.1051/itmconf/20171002007
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-lag Analysis of Longitudinal Associations between Non-verbal Intelligence and Math Achievement

Abstract: Abstract. The article presents the results of a longitudinal study of the relationship of nonverbal intelligence with success in teaching mathematics. A cross-lag analysis showed that at primary school age the empirical data is best described with the theoretical model of indirect influence of non-verbal intelligence. According to this model, nonverbal intelligence measured at Grade 3 of schooling affects the success in mathematics by the end of Grade 3, which, in turn, influences the success in mathematics by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Gygi et al (2017) carried out a study with different intelligence tests as a result of which it was determined that the intelligence tests predict school grades at a significant level. Tikhomirova et al (2017) found a significant link between non-verbal intelligence test scores and achievement in mathematics. A meta-analytical review conducted by Peng et al (2019) reported that fluid intelligence is moderately associated with reading skills and mathematics achievement.…”
Section: Discussionmentioning
confidence: 87%
“…Gygi et al (2017) carried out a study with different intelligence tests as a result of which it was determined that the intelligence tests predict school grades at a significant level. Tikhomirova et al (2017) found a significant link between non-verbal intelligence test scores and achievement in mathematics. A meta-analytical review conducted by Peng et al (2019) reported that fluid intelligence is moderately associated with reading skills and mathematics achievement.…”
Section: Discussionmentioning
confidence: 87%
“…The studies of the structure of the relationships between cognitive characteristics and individual differences in academic achievement in different sociocultural samples show directly opposite results (e.g., Tikhomirova et al, 2017a;Deary et al, 2007).…”
Section: Problem Statementmentioning
confidence: 99%